Investigation of the influence of the main dimensional ratios of a ship on the added resistance and drift force in short waves - Mourkogiannis, Dimitris (2022)
This study investigates analytically the influence of the length to draft and beam to draft ratio of a ship on the drift forces acting on a body in relatively short waves (small wavelength to ship length ratio). For validation, the proposed method is applied to predict the drift forces acting on simple geometries and real ships, yielding satisfactory predictions of the drift forces in both longitudinal and lateral directions. The proposed method can be applied to preliminary design tasks as it can capture the effect of the variation of a body’s dimensional ratios and the influence of incident wave direction.